Assessment of novel causes and investigation into the gut microbiome in cats with chronic kidney disease - Summers, Stacie, author; Lappin, Michael, advisor; Quimby, Jessica, committee member; Dow, Steve, committee member; Prenni, Jessica, committee member (Colorado State University. Libraries, 2020)
To view the abstract, please see the full text of the document.
Keywords: chronic kidney disease; microbiome; trimethylamine-n-oxide; indoxyl sulfate; cat; p-cresol sulfate